Efficacy of wax‐based bait stations for controlling Bactrocera dorsalis (Diptera: Tephritidae). Issue 8 (10th June 2022) - Lin, Jia; Hao, Xuxing; Yue, Guoqing; Yang, Deqing; Lu, Ningfeng; Cai, Pumo; Ao, Guofu; Ji, Qinge
Abstract: BACKGROUND: Bactrocera dorsalis is a notorious pest and spraying of insecticides has been the major approach to controlling its damage. However, insecticide abuse has led to negative impacts on public health and insecticide resistance; hence, sustainable strategies, such as bait stations, need to be developed and taken into account for B. dorsalis management. In this study, we integrated insecticide, sugar, olfactory and visual elements into a wax matrix to formulate a long‐lasting bait station. We determined its efficacy against B. dorsalis under field conditions. RESULTS: The optimal bait station was a wax matrix incorporated with 1% spinetoram, 1% yellow pigment, and 3% ammonium acetate, and was spherical in shape with a 6 cm diameter. The longevity of this bait station was at least 10 weeks under field conditions. In a release and recapture experiment performed in Orchard 1, the bait stations were as effective as bait spray in controlling sterile fly populations, and more effective than the control. In a 2‐year field trial conducted in Orchard 2, the number of female B. dorsalis and fruit infestation in the area where bait stations had been deployed was similar to the areas treated with cover spray. In Orchard 3, deployment of bait stations combined with chemical cover spray treatment decreased the population of female B. dorsalis and fruit damage more effectively than cover spray alone. CONCLUSIONS: Overall, wax‐based bait stations can be regarded as a viable alternative to insecticides or a synergistic method for managing B. dorsalis . © 2022 Society of Chemical Industry. Abstract : Integrating insecticide and various stimulating elements into wax to form long‐lasting bait station. Bait station is a viable alternative to insecticide or a synergist for managing Bactrocera dorsalis .